2009
DOI: 10.1128/iai.01039-08
|View full text |Cite
|
Sign up to set email alerts
|

Role of Deoxyribose Catabolism in Colonization of the Murine Intestine by PathogenicEscherichia coliStrains

Abstract: We previously suggested that the ability to metabolize deoxyribose, a phenotype encoded by the deoK operon, is associated with the pathogenic potential of Escherichia coli strains. Carbohydrate metabolism is thought to provide the nutritional support required for E. coli to colonize the intestine. We therefore investigated the role of deoxyribose catabolism in the colonization of the gut, which acts as a reservoir, by pathogenic E. coli strains. Molecular and biochemical characterization of 1,221 E. coli clone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 50 publications
0
35
0
Order By: Relevance
“…This gene was present in 48.15% of pathogenic isolates (52/108) and 15% of commensal strains (19/127); this difference was found to be significant (P Ͻ 0.0001) in 2 analysis. The presence and expression of the deoK operon had previously been investigated in all the strains of the collection (32). For confirmation of the linkage of the two loci observed during genome comparison, we amplified the region between the vpeC and deoM genes by PCR with the vpeC-F and deoM-F primers (see Tables S1 and S2 in the supplemental material and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This gene was present in 48.15% of pathogenic isolates (52/108) and 15% of commensal strains (19/127); this difference was found to be significant (P Ͻ 0.0001) in 2 analysis. The presence and expression of the deoK operon had previously been investigated in all the strains of the collection (32). For confirmation of the linkage of the two loci observed during genome comparison, we amplified the region between the vpeC and deoM genes by PCR with the vpeC-F and deoM-F primers (see Tables S1 and S2 in the supplemental material and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In most cases, the vpe and deoK loci are strongly linked (Ͼ75% association). We previously showed that the deoK operon encodes proteins involved in deoxyribose utilization and was acquired by horizontal transfer from Salmonella enterica (6,32). The high level of similarity between the vpe locus and a chromosomal sequence in Yersinia (75% identical to the sequence of Y. enterocolitica strain 8081) and its GϩC content of 46.8% suggested that E. coli acquired this sequence from Yersinia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations